2013
DOI: 10.1071/ah11108
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Australian healthcare sector’s responsiveness to environmental sustainability issues: suggestions from Australian healthcare professionals

Abstract: By implementing the strategies described, a more cohesive effort to address sustainability issues across the sector can be made. This may improve local and global health, within current and future generations. WHAT IS KNOWN ABOUT THE TOPIC? Healthcare has a significant impact on the natural and social environments, which in turn have a significant impact upon health and healthcare. WHAT DOES THIS PAPER ADD? This paper describes strategies to alter healthcare to better support environmental sustainability. WHAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…12,13 This led to discussions of personal and professional perspectives of environmentally responsible behaviour, and the different actions taken in these contexts. Interviews were recorded and transcribed verbatim.…”
Section: Data Collectionmentioning
confidence: 99%
“…12,13 This led to discussions of personal and professional perspectives of environmentally responsible behaviour, and the different actions taken in these contexts. Interviews were recorded and transcribed verbatim.…”
Section: Data Collectionmentioning
confidence: 99%
“…Two studies of pro‐environmental behaviours in the Australian and UK public health sectors found that employees were aware of the significant impact of healthcare delivery on the social and natural environments, as well as how social and natural environments impact upon health. However, both studies showed little evidence of employee pro‐environmental workplace behaviours with study participants citing organisational factors such as organisational structures, organisational culture and budgetary constraints as being the major barriers. In contrast, participants in this study did not demonstrate awareness of the environmental impacts of health care.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of adequate infrastructure (e.g. recycling facilities) and environmental information has also been identified as barriers to pro‐environmental workplace behaviours in the public healthcare sector in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Interprofessional rivalries serve to complicate the organizational landscape and can cause disparity between practice and professional and personal values. 2,[17][18][19] Researchers have found striking differences in the ways in which managers and clinicians perceive reform efforts in relation to financial restrictions, professional autonomy and work processes. 18,19 It has been posited that health services are currently operating within a dominant paradigm of reactivity.…”
Section: Characteristics and Realities Of Health Servicesmentioning
confidence: 99%
“…2,3,22,23 Policy, financial and regulatory environment Health services operate in a controlled legislative and regulatory environment required for optimal clinical care delivery and outcomes. 17 Key elements of that environment can impede the application of climate mitigation efforts.…”
Section: Contextual Determinants Of Sustainable Development In Healthmentioning
confidence: 99%